Chemical analyses of the seeds of some forage legumes from Turkey. A chemotaxonomic approach - Kocak, A.; Kokten, K.; Bagci, E.; Akcura, M.; Hayta, S.; Bakoglu, A.; Kilic, O. (Consejo Superior Investigaciones Cientificas-Csic, 2011)
The seeds of six forage legumes (Leguminosae) were investigated for their protein, tannin contents and fatty acid compositions. The protein contents of forage legume seeds were found to be between 23.1 and 37.2%. On the other hand, the tannin contents of the same seeds were found to be between 0.67 and 6.33%. The fatty acid compositions of these six different species were determined by gas chromatography of the methyl esters of their fatty acids. The seed oils of different Leguminous taxa contained linoleic and linolenic acids as their major components. The seed oils of Lathyrus annuus, Onobrychis crista-galli, Trigonella foenum-graceum, Lotus comiculatus, and Leuceana leucocephala species contain 50.0, 59.4, 69.5, 37.06, and 52.6% linoleic acid, respectively, as the major component fatty acids, whereas in the seed oil of Lathyrus cicer, linolenic acid accounts for 29.7% as the major component fatty acid. The ratios of these fatty acids in the Leguminous genera were found to be highly variable. In the study of taxa, palmitic acid was found in the major saturated fatty acids, on the other hand oleic, linoleic and linolenic acids were found in major unsaturated fatty acids.
Keywords: Fatty acid; Leguminosae; Protein; Seed oil; Tannin